Towards a sustainable valorisation of spilled oil by establishing a green chemistry between a surface active moiety of chitosan and oils - Doshi, Bhairavi (Lappeenranta-Lahti University of Technology LUT, 2019)
This thesis presents fabrication of sustainable surfactants from bio-polymer and demonstrates their performance in dispersion of spilled oil with different quality of water and climatic conditions, to provide a sustainable environmental technology for the oil spill treatment. One of the biggest threats to marine ecosystem is an oil spill, since the presence of an abundant amount of hydrocarbons alters the natural phenomenon of marine creatures. Moreover, for Arctic regions, the harsh climatic conditions and remoteness make the oil spill response more challenging. Various oil spill response techniques such as skimmers, booms, in-situ burning and dispersants were used. For large spill, mechanical methods are too slow to respond in the cold ice-affected waters and therefore, the most feasible response option is chemical surfactant. However, despite of their effectiveness, the use of synthetic dispersing agents such as Corexit 9527 and 9500 are proven to be more toxic than spilled oil. Therefore, an eco-friendly and sustainable approach towards the environment has introduced many non-toxic and biodegradable materials, such as cellulose and chitosan, for the removal and recovery of oil from water resources. Chitin is the second most abundant natural polymer obtained from crustaceans of crabs, lobsters and shrimps. Chitosan, which has two surface-active functional groups, hydroxyl and amino groups, is obtained from the deacetylation of chitin. In this work, these groups were modified via carboxymethylation and acylation to enhance the water solubility and hydrophobicity of chitosan. These modification routes can provide potential surfactant properties on chitosan as the polar chitosan skeleton will likely orientate towards the water phase and non-polar alkyl-groups towards the oil phase in oil-water system enabling dispersion of oil droplets. The decrease in temperature enlarged the oil droplet size. The formation of emulsion by breaking the oil in seawater requires more amount of chitosan materials than deionized ...